PENGEMBANGAN E-BOOK INTERAKTIF UNTUK PEMBELAJARAN FISIKA SMP - Darlen, Rikma Fitrialeni; Sjarkawi, Sjarkawi; Lukman, Aprizal (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2015)
This article is based on the development and design research. The research objective is (1) to develop interactive e-book physics that has pictures, video, animation, simulation, and voice as a source of learning physics (2) to develop interactive e-book of physics that can increase students' interest in learning physics. Model development used ADDIE model is proposed by Lee and Owens. Procedure development include: analysis, design, development, implementation, and evaluation. The results of individual trials and a small group of students at SMP Sari Putra Kota Jambi. Testing large group obtained an average value of 3.23 with the corresponding criteria/ right/ good/ easy. Based on the results of individual trials, small and large groups obtained in this study concluded that the interactive e-book for junior high school physics lessons appropriate for use as a source of learning physics junior level. Keyword: interactive e-book, learning physics